Development of a~motivation-trust-vulnerability (MTV) framework for cross-border online shopping: A~cross-national application to Chinese and German consumers - Gerhard Wagner; Anne Fota; Hanna Schramm-Klein; Sascha Steinmann (Schmalenbach Journal of Business Research (SBUR), 2023)
Building on the motivation-ability (MA) theoretical framework, we develop a motivation-trust-vulnerability (MTV) framework to explain behavioral decision making in situations of uncertainty and vulnerability. We apply our new framework to cross-border online shopping, which is characterized by uncertain benefits, potential losses, and increased vulnerability of making cross-border online purchases at foreign online vendors. The MTV framework (1) explains the mechanism of cross-border online shopping by considering the effects and interactions of motivation, trust, and vulnerability (2), offers a new conceptualization of perceived vulnerability and (3) is applicable to culturally and economically distinct country markets. The findings from two major e-commerce markets (China and Germany; N = 808) support our framework and suggest that perceived vulnerability acts as an obstacle that prevents consumers from cross-border online shopping. However, in interaction with trust towards foreign online vendors perceived vulnerability positively affects the relationship between motivating factors and cross-border online purchase intentions. Our findings help explaining consumers' cross-border online purchasing intentions and provide guidance for retail managers and policy makers on recognizing and coping with trust and vulnerability in international relations.
Keywords: 650; Consumer Behavior; Cross-Border E-Commerce; Distribution Channels; Retailing; Structural Equation Modeling